STRATEGI PENGEMASAN PESAN E-MARKETING PADA FOOD VLOGGER (Universitas Negeri Surabaya, 2022)
This study aims to determine how the e-marketing message packaging strategy on food vloggers through social media. Meanwhile, there is a content creator who has succeeded in being popular and liked by several audiences through the culinary review content he presents, namely Muhammad Almas Qalbi or a TikTok account with the username @almasqol. Almas is a pioneer food vlogger using TikTok as a platform. What makes Almas different from other food vloggers is how Almas uses cultural proximity in its e-marketing message packaging strategy on its social media. Submission of communication style by maximizing the use of East Javanese language is used as one of the identities formed on social media. Qualitative research methods using a case study approach are deemed appropriate to be used in this study. By conducting in-depth interviews with several sources related to the information needed by researchers. As a result, the East Javanese language swearing, which turned out to be liked by the audience, encouraged Almas to voice his slogans in every video. Various kinds of content are uploaded by prioritizing the unique message packaging aspect, namely using the East Javanese language with a distinctive medok accent. Message packaging still prioritizes how the content of the message is conveyed by combining several aspects such as rationality, freedom of expression (customization), humor, entertainment (entertain), interaction, trends and word of mouth. Almas uses cultural closeness in terms of the area of origin and also the East Javanese language as a characteristic that is identical to it. Keywords : Message Packaging Strategy, E-Marketing, Food Vlogger, TikTok